2002
DOI: 10.1001/archpedi.156.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Violence-Related Injuries in Boston

Abstract: Context: Violence-related injuries among children are common, but age-based incidence data are not easily available.Objectives: To describe injuries due to violence in a population-based case series of children and to estimate injury incidence.Design: Prospective surveillance of children residing in Boston, Mass, who received pediatric emergency department treatment for violence-related injury during a 4-year period beginning April 15, 1995.Setting: Pediatric emergency departments in Boston.Patients: Children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In our study, the occurrence of VRPI was statistically significant and more common among men than women (OR = 2.66, 95% CI 1.14-6.23). Based on gender, other studies confirmed our results nationally ( 17 , 18 , 27 ) and internationally ( 20 , 25 ). In our study, the most frequently injured organs were the upper limbs followed by head and neck.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, the occurrence of VRPI was statistically significant and more common among men than women (OR = 2.66, 95% CI 1.14-6.23). Based on gender, other studies confirmed our results nationally ( 17 , 18 , 27 ) and internationally ( 20 , 25 ). In our study, the most frequently injured organs were the upper limbs followed by head and neck.…”
Section: Discussionsupporting
confidence: 90%
“…In the USA, VRPI was reported to be 7.56 per 1000 population in 2011 and 7.59 per 1000 population in 2010 ( 19 ). In Boston, VRPI for children aged 3-18 years was estimated at 5.27 (95% CI: 5.05-5.49) in 2002 ( 20 ). In Iran, based on Rahimi-Movaghar’s study, the incidence of VRPI was estimated at 0.77 per 1000 population among 44 cities with 100000-200000 population ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…A Boston pediatric ED surveillance study demonstrated that only 6.4% of patients requiring treatment for violence-related injuries required hospital admission. 17 In an Israeli study of youth, 84% were discharged directly from the ED. 18 This high percentage of direct ED discharges highlights the fact that ED staff are often the only health care workers who treat patients after violent injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the likelihood of abusive injury requiring urgent medical care, maltreatment victims as a group were hypothesized to experience greater severity of injury, likelihood of hospitalization, and risk of death in the ED than that of nonmaltreated children (Gilbert et al, 2009;Rovi, Chen, & Johnson, 2004). Similarly young children who presented to the ED for physical abuse were hypothesized to be younger, to have sustained more severe injuries, and to be at greater risk of hospitalization and death in the ED setting than children who experienced other types of maltreatment (Sege et al, 2002). Because personnel in the ED primarily focus on stabilizing emergent patients, recognition and diagnosis of neglect were expected to be less commonly identified in the ED than in physical abuse.…”
mentioning
confidence: 99%